The concise new Partridge dictionary of slang and unconventional English - Partridge, Eric, 1894-1979 (Routledge, 2015)
"The Concise New Partridge Dictionary of Slang presents all the slang terms from The New Partridge Dictionary of Slang and Unconventional English in a single volume. Containing over 60,000 entries from around the English-speaking world, this concise new edition of the authoritative work on slang details the slang and unconventional English of the English-speaking world since 1945, and through the first decade of the new millennium, with the same thorough, intense, and lively scholarship that characterized Partridge's own work. Unique, exciting and, at times, hilariously shocking, key features include: unprecedented coverage of World English, with equal prominence given to American and British English slang, and entries included from Australia, New Zealand, Canada, India, South Africa, Ireland, and the Caribbean - emphasis on post-World War II slang and unconventional English - dating information for each headword New to this second edition: A new preface noting slang trends of the last five years - Over 1,000 new entries from the US, UK and Australia, reflecting important developments in language and culture - New terms from the language of social networking from a range of digital communities including texting, blogs, Facebook, Twitter and online forums Many entries now revised to include new dating, ensuring maximum accuracy of content"--Resumé vydavatele